2018
DOI: 10.1155/2018/2425619
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Jatropha and Pongamia Oil Based Environmentally Friendly Cutting Fluids for Turning AA 6061

Abstract: Owing to the desirable properties of vegetable oils as cutting fluids, an attempt is made to explore the potentiality of plentifully available vegetable oils as a cutting fluid for turning AA 6061. Two nonedible vegetable oils, Jatropha and Pongamia, in their chemically modified (epoxidized) versions are used as straight cutting fluids. Cutting fluids are introduced to the machining zone with the aid of Minimal Quantity Lubrication (MQL) method. Taguchi's technique of orthogonal arrays is used to develop an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…Waste cooking palm oil essentially consists of triglycerides, unsaturated fatty acids, with glycerol [6,17,23,24], water, and other impurities. Water is responsible for degradation of oils and additives via hydrolysis, and ester-based lubricating oils are susceptible to attack by water resulting in the production of acids and alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…Waste cooking palm oil essentially consists of triglycerides, unsaturated fatty acids, with glycerol [6,17,23,24], water, and other impurities. Water is responsible for degradation of oils and additives via hydrolysis, and ester-based lubricating oils are susceptible to attack by water resulting in the production of acids and alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…They observed decreases in friction coefficient with the enhancement of pin speed. In another study, Jeevan and Jayaram (2018) found MJO and Pongamia oils with the aid of MQL performed better than petroleum based oil in terms of cutting force, surface roughness during turning of aluminium. Nizamuddina et al (2018) compared karanja based cutting fluid with conventional fluid during turning of AISI1045 steel with coated carbide tool and observed 11 per cent reduction in chip thickness which directly linked with the enhanced tool life.…”
Section: Introductionmentioning
confidence: 93%
“…Bio-based lubricant are biodegradable, non-toxic, have good lubricity, provide high strength lubricant film, have a higher flash point, higher viscosity index, low evaporative losses and better boiling point, as a result, there is a minimal loss from misting (Mannekote et al, 2017). Further, due to the immense gap in demand and supply of edible vegetable oils (coconut, palm, soya bean and canola oil), non-edible bio-oils or lubricants like karanja, linseed and JCO are finding significance because of their ample quantity and also, this would save large quantities of edible oils which are in great demand (Jeevan and Jayaram, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The vegetable oil based emulsified cutting fluids would ultimately reduce the cost contribution of cutting fluid on the total manufacturing cost and would eliminate the pollution caused by the oil waste fed on the environment [1] , [2] , [3] , [4] .…”
Section: Data Descriptionmentioning
confidence: 99%